Sustainable winner determination for public-private partnership infrastructure projects in multi-attribute reverse auctions - Gao, Guang-Xin (2018)
Selection of a sustainable private partner (contractor) is significant to ensure the success of public-private partnership (PPP) projects. In recent years, multi-attribute reverse auctions (MARAs) are widely used in public procurement to select the desirable contractor. However, the MARA mechanism is neglected in the existing studies. The purpose of this paper is to present a MARA framework for selecting a sustainable contractor in PPP infrastructure projects, in which the MARA rules and an integrated winner determination method are involved. In particular, the sustainability considerations are incorporated in the MARA rules, which can make the potential contractors have incentives to improve their sustainable performance. Within the MARA rules, based on the trapezoidal fuzzy linguistic representation model and the classical two-additive Choquet (TAC) integral operator, a winner determination method is developed to evaluate and rank potential contractors, in which both the bid evaluation and the interrelationships among bid evaluation attributes are considered. Finally, the potential of the proposed method is shown through an illustrative case of a PPP project of a subway construction in China. The MARA framework investigated helps governments make reliable decisions in sustainable procurement and thereby facilitates successful project delivery.